Nonalcoholic steatohepatitis in posttransplantation liver: Review article - Andrade,Antônio Ricardo Cardia Ferraz de (2018)
Summary Introduction: Nonalcoholic steatohepatitis (NASH) associated or not with cirrhosis is the third leading indication for liver transplantation (LT) around the world. After transplants, NASH has a high prevalence and occurs as both recurrent and de novo manifestations. De novo NASH can also occur in allografts of patients transplanted for non-NASH liver disease. Objective: To evaluate recurrent or de novo NASH in post-LT patients. Method: A literature review was performed using search engines of indexed scientific material, including Medline (by PubMed), Scielo and Lilacs, to identify articles published in Portuguese and English until August 2016. Eligible studies included: place and year of publication, prevalence, clinical characteristics, risk factors and survival. Results: A total of 110 articles were identified and 63 were selected. Most of the studies evaluated recurrence and survival after LT. Survival reached 90-100% in 1 year and 52-100% in 5 years. Recurrence of NAFLD (steatosis) was described in 15-100% and NASH, in 4-71%. NAFLD and de novo NASH were observed in 18-67% and 3-17%, respectively. Metabolic syndrome, diabetes mellitus, dyslipidemia and hypertension were seen in 45-58%, 18-59%, 25-66% and 52-82%, respectively. Conclusion: After liver transplants, patients present a high prevalence of recurrent and de novo NASH. They also show a high frequence of metabolic disorders. Nevertheless, these alterations seem not to influence patient survival.